Interleukin (IL)-9/IL-9R axis drives γδ T cells activation in psoriatic arthritis patients. (21st October 2016) - Guggino, G; Ciccia, F; Di Liberto, D; Lo Pizzo, M; Ruscitti, P; Cipriani, P; Ferrante, A; Sireci, G; Dieli, F; Fourniè, J J; Giacomelli, R; Triolo, G
Summary: Cytokines such as tumour necrosis factor (TNF)-α, interleukin (IL)-12, interferon (IFN)-γ, IL-23 and, more recently, IL-9, have been implicated in the initiation/maintenance of inflammation in psoriasis and psoriatic arthritis (PsA). In the present study we aimed to characterize the role of γδ T cells in peripheral blood and synovial fluid of PsA patients and to investigate their response to in-vitro stimulation with antigen or cytokines (IL-9 and IL-23). γδ T cells isolated from peripheral blood mononuclear cells and synovial fluid were analysed by flow cytometry to evaluate the phenotype and cytokine production. IL-23R and IL-9R gene expression were also evaluated by reverse transcription–polymerase chain reaction (RT–PCR). Peripheral blood mononuclear cells (PBMC), sorted γδ T cells and γδ cell lines were also stimulated in vitro with isopentenyl pyrophosphate (IPP), recombinant IL-9 or recombinant IL-23. Our results show an expansion of γδ T cells with a predominant effector memory phenotype in peripheral blood and synovium of untreated PsA patients, which reverses significantly after treatment with anti-TNF-α or anti-IL-12/IL-23R monoclonal antibodies (mAbs). Moreover, in PsA patients γδ T cells activation is driven prevalently by IL-9/IL-9R interaction, and not only by IL-23/IL-23R. Together these findings indicate γδ T cells and IL-9 as new players in the pathogenesis of PsA. Graphical Abstract: